2022
DOI: 10.3390/s22072494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electroporation Medium on Delivery of Cell-Impermeable Small Molecules by Electrical Short-Circuiting via an Aqueous Droplet in Dielectric Oil: A Comparison of Different Fluorescent Tracers

Abstract: Membrane permeabilization stimulated by high-voltage electric pulses has been used to deliver cell-impermeable exogenous molecules. The electric field effect on the cells depends on various experimental parameters, such as electric field strength, the number of electric pulses, and the electroporation medium. In this study, we show the influence of the electroporation medium on membrane permeabilization stimulated by electrical short-circuiting via an aqueous droplet in dielectric oil, a novel methodology deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…We have also investigated the mechanisms of gene electrotransfection using short-circuiting via an aqueous droplet (Fig 1) [17,18]. A previous investigation demonstrated that electrical stimulation increases transient membrane permeability to calcium ions and cellimpermeable nucleic acid-binding fluorescent dyes (YO-PRO-1), indicating transient membrane pore formation [17]. Short-circuiting using a low-conductivity electroporation medium enhanced the formation of both transient and irreversible membrane pores.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…We have also investigated the mechanisms of gene electrotransfection using short-circuiting via an aqueous droplet (Fig 1) [17,18]. A previous investigation demonstrated that electrical stimulation increases transient membrane permeability to calcium ions and cellimpermeable nucleic acid-binding fluorescent dyes (YO-PRO-1), indicating transient membrane pore formation [17]. Short-circuiting using a low-conductivity electroporation medium enhanced the formation of both transient and irreversible membrane pores.…”
Section: Plos Onementioning
confidence: 99%
“…The droplet electroporation apparatus was fabricated as described in our previous papers [17,18]. The apparatus consisted of pin headers and a printed circuit board, and the gap between the electrodes was 5.08 mm.…”
Section: Experimental Setup and Electrical Short-circuiting Via A Cel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose has also been used in drug and gene delivery [ 13 , 14 , 15 ]. One of its applications is in improving electrotransfer (ET) [ 14 , 16 , 17 ], which is a technology for the delivery of molecular cargo, including DNA, RNA, protein, and ribonucleoprotein (RNP) [ 18 , 19 , 20 ]. ET is cost-effective, versatile, multiplexable, and applicable to almost all cell types [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually performed with the help of specially formulated buffers to achieve optimal cell viability and delivery efficiency [ 23 ]. Sucrose has been used as an important component in ET buffers as an osmotic balancing agent [ 14 , 16 , 17 ]. Recently, we discovered that ET efficiency could be enhanced through the pretreatment of cells with sucrose in vitro [ 24 ], partly due to the formation of large, amphisome-like bodies (ALBs) and enlargement of lysosomes.…”
Section: Introductionmentioning
confidence: 99%